FABRICATION OF BOLT CLAMPED LANGEVIN ULTRASONIC TRANSDUCER FOR HOMOGENIZER BY CONTROLLING PIEZOCERAMIC PRE-STRESS - Nurul Khairiyah, Aisyah
esign of high power ultrasonic transducers for homogenizing sonication applications. Ultrasonic homogenization with the phenomenon of cavitation formed in liquids due to the vibrations it generates, is one of the tools that is widely used in various processes, even in sonochemistry, cell lysis to nanoparticle synthesis. An ultrasonic homogenizer, often called a sonicator, consists of an ultrasonic generator, an ultrasonic transducer or converter, a mechanical booster and a horn or probe (sonotrode) with a resonant frequency at 20 kHz. This study aims to design the optimization of ultrasonic transducers. Material selection, geometry optimization and mechanical resistance are among the problems that become a concern in the transducer design process. In addition, the process of tightening or applying prestress during the assembly of the transducer greatly affects the performance of the transducer. In this research, the design and performance characterization will be carried out with the aim of obtaining an effective and efficient transducer and sonotrode design process. This research includes initializing the design analytically using mathematical equations, simulation using Finite Element Analysis (FEA) and optimizing the design, followed by experimental testing. The experimental results that have been matched, namely the ultrasonic transducer with a frequency of 20 kHz will be the benchmark in prototyping. From the simulation results and measurements, the series resonant frequency, electrical impedance, and effective electromechanical coupling for a 16×13 mm radiator configuration transducer are 20.15 kHz, 100 ?, and 0.2229 from the simulation results, while 20.17 kHz, 24.91 ?, and 0.2033 obtained from the measurement results at 15 kN prestress conditions or identical to 24 N.m torque. A percentage of 0.01% was obtained from the difference in resonant frequency between the simulation and experimental results for this transducer.